Chemical and absorption signatures of Xiao Chai Hu Tang. (10th June 2018) - Du, Ting; Zeng, Min; Chen, Li; Cao, Zheng; Cai, Hua; Yang, Guangde
Abstract : Rationale: Xiao Chai Hu Tang (XCHT, Sho‐saiko‐to in Japanese) is a well‐known medicine formula that has been used in Asia for centuries. However, the quality control and the absorption of XCHT components are the major remaining concerns. The study aimed to develop a sensitive and robust method to characterize the chemical components in XCHT and evaluate their absorptions. Methods: Ultra‐high‐pressure liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight mass spectrometry (UHPLC/ESI‐QTOF‐MS/MS) was used to identify the compounds in XCHT. The Caco‐2 cell culture model was employed to determine the absorption of the identified components. Results: The results showed that 109 compounds were identified including organic acids, flavonoids, saikosaponins, ginsenosides, licoricesaponins and gingerols. The absorption study showed that among those identified, 33 compounds have decent absorption permerbilities ranging from 1.46 ± 0.24 × 10 −7 to 3.10 ± 0.61 × 10 −5  cm/s. These compounds were classified as classes II and IV in the biopharmaceutical classification system (BCS). Conclusions: These identified compounds could be used to characterize the quality of XCHT and those absorbed compounds with decent permreabiliteis are the potential active components in XCHT. Future pharmacodynamics studies should focus on these absorbed compounds.